Local Government Strategies in Maintaining the Quality of Public Services Following Budget Efficiency Policies : A Study of the Mojokerto Regency Government, Bekasi City Government, and Blora Regency Government - Abdul Hakim; Arief Rachmat Fauzi; Yacinta Stefila Paramawati (JURNAL SAINS SOSIAL DAN HUMANIORA (JSSH), 2025)
This study aims to analyze local government responses to the budget efficiency policy mandated by Presidential Instruction No. 1 of 2025. The research focuses on three regions in Java Island; Mojokerto Regency, Bekasi City, and Blora Regency which represent varying levels of budget efficiency impact. Using a qualitative descriptive approach and case study method with data triangulation, the study finds that the effectiveness of budget efficiency policies is strongly influenced by three main factors: good governance, political stability, and bureaucratic capacity. Each region adopted distinct strategies to sustain public services, including digitalization, prioritization of essential sectors, and political negotiation. The findings suggest that the success of efficiency policies largely depends on local fiscal capacity and coordination among key stakeholders. The study recommends that the central government provide clearer technical guidelines and strengthen fiscal capacity and public participation at the local level.